Going with the wind: adaptive dynamics of plant secondary meristems - Agusti, Javier; Greb, Thomas (Mechanisms of development, 2012)
The developmental plasticity of organisms is a natural consequence of adaptation. Classical approaches targeting developmental processes usually focus on genetics as the essential factor underlying phenotypic differences. However, such differences are often based on the inherent plasticity of developmental programs. Due to their dependence on environmental stimuli, plants represent ideal experimental systems in which to dissect the contribution of genetic and environmental variation to phenotypic plasticity. An evident example is the vast repertoire of growth forms observed in plant shoot systems. A fundamental factor underlying the broadness of this repertoire is the activity of secondary meristems, namely the axillary meristems that give rise to side shoots, and the cambium essential for stem thickening. Differential activities of both meristem types are crucial to the tremendous variation seen in higher plant architecture. In this review, we discuss the role of secondary meristems in the adaptation of plant growth forms, and the ways in which they integrate environmental input. In particular, we explore potential approaches for dissecting the degree to which this flexibility and its consequences for plant architecture is genetically predetermined and how much it represents an adaptive value.